The bidirectional relationship between anxiety disorders and circulating levels of inflammatory markers: Results from a large longitudinal population‐based study. Issue 4 (15th December 2017) - Glaus, Jennifer; von Känel, Roland; Lasserre, Aurélie M.; Strippoli, Marie‐Pierre F.; Vandeleur, Caroline L.; Castelao, Enrique; Gholam‐Rezaee, Mehdi; Marangoni, Ciro; Wagner, En‐Young N; Marques‐Vidal, Pedro; Waeber, Gérard; Vollenweider, Peter; et al.
Abstract : Background: Although there has been abundant research on chronic low‐grade inflammation as a potential mechanism underlying the link between mood disorders and cardiovascular risk, less is known about the role of inflammatory factors and anxiety disorders. The aim of this paper is to evaluate the bi‐directional associations between inflammatory markers including interleukin (IL)‐6, tumor necrosis factor (TNF)‐α, and high sensitivity C‐reactive protein (hsCRP) with anxiety disorders and its subgroups. Methods: The sample consisted of 3, 113 participants (53.7% women; mean age: 51.0, S.D. 8.8 years), randomly selected from the general population, who underwent comprehensive somatic and psychiatric evaluations at baseline and follow‐up (mean follow‐up duration = 5.5 years, S.D. 0.6). Anxiety disorders were assessed with semistructured diagnostic interviews. Inflammatory biomarkers were analyzed in fasting blood samples. Results: After adjustment for potential confounders, current anxiety disorders ( β = 0.09, 95% CI 0.00–0.17) and agoraphobia ( β = 0.25, 95% CI: 0.07–0.43) at baseline were associated with a steeper increase of hsCRP levels over the follow‐up period. Current posttraumatic stress disorder (PTSD) was associated with a lower increase of IL‐6 levels over the follow‐up period ( β = −0.52, 95% CI: −1.00/−0.04). There was no evidence for an association between inflammation markers at baseline and anxiety disorders at follow‐up. Conclusions: The prospective association between agoraphobia at baseline and hsCRP levels over the follow‐up period suggests that chronic low‐grade inflammation may be a consequence of this condition. The decrease in IL‐6 in PTSD also requires further investigation. No evidence was found for chronic low‐grade inflammation as a predictor of future anxiety disorders.